Technique of “mini-invasive radical antegrade modular pancreatosplenectomy” for pancreatic cancer - Zimmitti, Giuseppe; Manzoni, Alberto; Garatti, Marco; Sega, Valentina; Rosso, Edoardo (Digestive Medicine Research; Vol 1 (October 2018): Digestive Medicine Research, 2018)
Pancreatic cancer spreads preferentially into the retroportal lamina that is frequently invaded at the celiac trunk (CT) and/or superior mesenteric artery (SMA) margins. In 2007, for the first time, it has been proposed by the team of Prof. Strasberg SM an innovative surgical technique for open surgery called radical antegrade modular pancreatosplenectomy (RAMPS) which allows to increase the circumferential resection margins in case of pancreatic cancer of the body of the pancreas and it is associated to a high rate of R0 resection. Currently, it is possible to perform such intervention mini-invasively. The present manuscript reports our technique.